High‐performance macromolecular data delivery and visualization for the web. Issue 12 (2nd December 2020) - Sehnal, David; Svobodová, Radka; Berka, Karel; Rose, Alexander S.; Burley, Stephen K.; Velankar, Sameer; Koča, Jaroslav
Abstract : This article provides a survey of available web services and tools for data delivery and visualization of macromolecular structures. Abstract : Biomacromolecular structural data make up a vital and crucial scientific resource that has grown not only in terms of its amount but also in its size and complexity. Furthermore, these data are accompanied by large and increasing amounts of experimental data. Additionally, the macromolecular data are enriched with value‐added annotations describing their biological, physicochemical and structural properties. Today, the scientific community requires fast and fully interactive web visualization to exploit this complex structural information. This article provides a survey of the available cutting‐edge web services that address this challenge. Specifically, it focuses on data‐delivery problems, discusses the visualization of a single structure, including experimental data and annotations, and concludes with a focus on the results of molecular‐dynamics simulations and the visualization of structural ensembles.